Differences in Fecal Gut Microbiota, Short-Chain Fatty Acids and Bile Acids Link Colorectal Cancer Risk to Dietary Changes Associated with Urbanization Among Zimbabweans. (17th November 2019) - Katsidzira, L.; Ocvirk, S.; Wilson, A.; Li, J.; Mahachi, C. B.; Soni, D.; DeLany, J.; Nicholson, J. K.; Zoetendal, E. G.; O'Keefe, S. J. D.
Abstract: The incidence of colorectal cancer (CRC) is gradually rising in sub-Saharan Africa. This may be due to dietary changes associated with urbanization, which may induce tumor-promoting gut microbiota composition and function. We compared fecal microbiota composition and activity in 10 rural and 10 urban Zimbabweans for evidence of a differential CRC risk. Dietary intake was assessed by a food frequency questionnaire. Fecal microbiota composition, metabolomic profile, functional microbial genes were analyzed, and bile acids and short chain fatty acids quantified. Animal protein intake was higher among urban volunteers, but carbohydrate and fiber intake were similar. Bacteria related to Blautia obeum, Streptococcus bovis, and Subdoligranulum variabile were higher in urban residents, whereas bacteria related to Oscillospira guillermondii and Sporobacter termitidis were higher in rural volunteers. Fecal levels of primary bile acids, cholic acid, and chenodeoxycholic acid ( P < 0.05), and secondary bile acids, deoxycholic acid ( P < 0.05) and ursodeoxycholic acid ( P < 0.001) were higher in urban residents. Fecal levels of acetate and propionate, but not butyrate, were higher in urban residents. The gut microbiota composition and activity among rural and urban Zimbabweans retain significant homogeneity (possibly due to retention of dietary fiber), but urban residents have subtle changes, which may indicate a higher CRC risk.